2020
DOI: 10.3390/jcm9103204
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Urate Deposition: An Unrecognized Complication of Gout?

Abstract: Gout, an inflammatory arthritis, affects over nine million people in the US with increasing prevalence. Some medical societies do not recommend treating gout unless it is recurrent. While soft tissue urate deposits (tophi), resultant bone erosions, and joint inflammation are frequently recognized in gout, urate crystal deposits in other sites have been thought to be rare. Recent diagnostic testing, such as dual energy computed tomography (DECT), has led to the recognition that urate deposits are not uncommon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 92 publications
(140 reference statements)
0
31
0
Order By: Relevance
“…As mentioned above, data on the natural history of gout (Fig. 1 ) are scarce but the application of modern imaging techniques, such as dual-energy CT, has led to the recognition of a pre-symptomatic phase of gout in some individuals in whom MSU crystal deposition occurs in joints, soft tissues and vascular sites before the first gout flare (asymptomatic MSU crystal deposition) 35 , 36 . Whether this pre-symptomatic phase is more common in people with CKD in whom the inflammatory response to crystals might be suppressed remains unknown, as does the timing of progression from asymptomatic to symptomatic gout in people with CKD.…”
Section: Issues With Studies Of Gout and Ckdmentioning
confidence: 99%
“…As mentioned above, data on the natural history of gout (Fig. 1 ) are scarce but the application of modern imaging techniques, such as dual-energy CT, has led to the recognition of a pre-symptomatic phase of gout in some individuals in whom MSU crystal deposition occurs in joints, soft tissues and vascular sites before the first gout flare (asymptomatic MSU crystal deposition) 35 , 36 . Whether this pre-symptomatic phase is more common in people with CKD in whom the inflammatory response to crystals might be suppressed remains unknown, as does the timing of progression from asymptomatic to symptomatic gout in people with CKD.…”
Section: Issues With Studies Of Gout and Ckdmentioning
confidence: 99%
“…In fact, both these vasoconstrictor molecules can be over-expressed in the presence of high UA concentrations, inducing the development of hypertension [65,79]. UA can also mediate the development of hypertension through a crystal-dependent pathway [80,81]. In fact, monosodium urate deposits have been found in the kidney medulla, cardiac valves, arteries, and within the atherosclerotic plaque [80,81].…”
Section: Biology Of the Association Between Ua And Hypertensionmentioning
confidence: 99%
“…UA can also mediate the development of hypertension through a crystal-dependent pathway [80,81]. In fact, monosodium urate deposits have been found in the kidney medulla, cardiac valves, arteries, and within the atherosclerotic plaque [80,81]. These deposits could lead to kidney injury and arterial stiffness, increasing the risk for hypertension [80,81].…”
Section: Biology Of the Association Between Ua And Hypertensionmentioning
confidence: 99%
“…Subjects with CKD and gout have more tophi than gouty subjects with normal kidney function (6-fold greater in stage 3 CKD) [38], suggesting they carry higher risk for extra-articular crystal deposits. Recently, it has been recognized that urate crystals can deposit in many locations, including the kidney, blood vessels, and spine [39]. One study reported that urate crystals are present in the aorta or coronary vessels in 80% of subjects with gout [40], where it can localize to plaques [41].…”
Section: Subgroups Of Ckd Where Lowering Uric Acid May Be Of Benefitmentioning
confidence: 99%